Transformaciones en la Matriz de Protección Uruguaya a Inicios del Siglo XXI = Transformations in the Uruguayan Protection Matrix at the Beginning of the 21st Century - González Laurino, Carolina; Leopold Costábile, Sandra (Textos & Contextos (Porto Alegre))
The Uruguayan social protection matrix implemented at the beginning of the 20th century has been described as a strongly institutionalized social policy system, structured on a universal basis in education and stratified in health and social security, which tends to cover the majority of urban salaried sectors, with a late incorporation of rural workers. This social protection structure has undergone a transformation process that combines state intervention with semi-privatized, focused and transient services, as well as others that appeal to the public-private configuration in its implementation process. To this end, among other actions, the programmatic proposals characterized by their intervention in «proximity» have been designed and put into practice, on which this study focuses its analysis